2020
DOI: 10.3389/fphys.2020.00551
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Neurovascular Control Underlies Declining Microvascular Functionality in People With Non-alcoholic Fatty Liver Disease (NAFLD) at Risk of Liver Fibrosis

Abstract: Background/Aims: Increasing evidence shows that non-alcoholic fatty liver disease (NAFLD) is associated with dysregulation of microvascular perfusion independently of established cardio-metabolic risk factors. We investigated whether hepatic manifestations of NAFLD such as liver fibrosis and liver fat are associated with microvascular hemodynamics through dysregulation of neurovascular control. Methods: Microvascular dilator (post-occlusive reactive hyperemia) and sympathetically mediated constrictor (deep ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…In another study of 496 individuals, Liu et al reported that HRV measures, as detected by 5-min resting electrocardiograms, were lower in individuals with ultrasounddetected NAFLD than in those without NAFLD (16). Similarly, Clough et al found that dysregulated neurovascular control underlined declining microvascular functionality in 189 patients with radiological or biopsy-proven NAFLD (17). A strong association between NAFLD (on ultrasonography) and impaired cardiac sympathetic/parasympathetic balance, regardless of the presence or absence of T2D and other cardiometabolic risk factors, was also recently confirmed in the Cooperative Health Research in South Tyrol-NAFLD substudy (n=356 individuals included) (18).…”
Section: Cardiac Autonomic Dysfunctionmentioning
confidence: 99%
“…In another study of 496 individuals, Liu et al reported that HRV measures, as detected by 5-min resting electrocardiograms, were lower in individuals with ultrasounddetected NAFLD than in those without NAFLD (16). Similarly, Clough et al found that dysregulated neurovascular control underlined declining microvascular functionality in 189 patients with radiological or biopsy-proven NAFLD (17). A strong association between NAFLD (on ultrasonography) and impaired cardiac sympathetic/parasympathetic balance, regardless of the presence or absence of T2D and other cardiometabolic risk factors, was also recently confirmed in the Cooperative Health Research in South Tyrol-NAFLD substudy (n=356 individuals included) (18).…”
Section: Cardiac Autonomic Dysfunctionmentioning
confidence: 99%
“…In a study including 46 UK patients with NAFLD, 16 patients with hepatic steatosis and excessive alcohol intake (i.e., having a dual aetiology fatty liver disease, DAFLD) and 34 control subjects, Houghton et al reported that both individuals with NAFLD and those with DAFLD had impaired CANS function (assessed by HRV measures using power spectral analysis) when compared to control subjects [20]. Similarly, in a study of 189 subjects with biopsy-proven NAFLD, it has been shown that dysregulated neurovascular control underlies declining microvascular functionality in adults with NAFLD, suggesting a mechanistic role for dysregulated neurovascular control of the vasculature in NAFLD [37]. Some small studies have also reported the presence of impaired heart recovery index after exercise (treadmill test) in individuals with NAFLD [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD composes a spectrum ranging from accumulation of fat in hepatocytes to progressive fibrosis, cirrhosis and liver failure [212][213][214][215][216][217]. Underlying dynamic causes are microvascular dysfunction [218][219][220][221][222][223][224][225][226][227][228][229][230], IR [231][232][233][234][235][236][237][238][239], mitochondrial dysfunction [240][241][242][243][244][245][246][247] and inflammation [248][249][250][251][252][253][254][255][256].…”
Section: Systemic Energy Deficitmentioning
confidence: 99%